The Effectiveness of Detecting Thematic Relations of Objects in 3–6 Year Old Children - Kurganskii, A. V.; Zakharova, M. N.; Kayumov, D. D.; Antonova, S. Yu (Human physiology, 2023)
In this study, the ability of preschoolers aged 3–6 to detect and understand the thematic connections of objects was assessed. Children (95 children; 53 girls and 42 boys) of four age groups of 3, 4, 5, and 6 years old (respectively, 17, 33, 18, and 27 children) solved two tasks aimed at the detection of thematic relations of objects within the framework of the standard “yes–no” procedure. In the first task, it was required to indicate whether the image of the shown object was relevant to a given context (the “object–context” task, O–C), and in the second, whether two objects were related thematically (the “object–object” task, O–O). A touch screen computer was used to present images and record motor responses. For each task, we measured the accuracy scores (the proportion of correct responses) and the delay in the motor response “yes” or “no” relative to the moment the image was presented (reaction time). Two components of the reaction time were analyzed separately: the duration of the latent phase and the duration of the overt movement towards the response button. With age, the accuracy of solving both tasks increased, and the time required to discover the thematic connection (reaction time) decreased. At the same time, the accuracy scores were lower, and the detection time was longer in the O–O task compared to the O–C. The gender of the child did not affect the accuracy value, and affected only the duration of the motor (but not the latent) phase of the motor response, and only in the O–O task. The data obtained show that (i) the O–O task is more difficult than the O–C task, and that this may be due to the necessity to activate the thematic links of two objects in the O–O task instead of just one, as in the O–C task, and (ii) the process of activation of thematic links probably does not end in the latent phase of the motor response and continues during its movement phase. The question of the extent to which the success and duration of the process of detecting the thematic links of objects can limit the success of cognitive planning in preschoolers aged 3–6 is also discussed.